Continuous Yet contentious: United Nations Agencies Roles and Mexico’s Adoption of Women’s Rights Protection Against Femicides (2018-2022) - Witri Elvianti; Nanda Satria (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2023)
In Mexico, violence against women remains a serious issue, especially femicide, which has occurredfor decades. This paper aims to explore the UN’s agencies' contribution to promoting the protectionof human rights through collective action to address sexual and gender-based violence in Mexico. Itmainly asks how the UN’s agency attempted to sustain the international moral standard of women’srights in Mexico amidst the alarming femicide crisis in this country. This paper is designed asqualitative research by applying a descriptive approach and using data from academic literature,reports, official websites, and newspaper publications. The analysts seek to argue that internationalorganizations, the UN – through its agencies, the OHCHR, and UN Women – have demonstrated theirrole as a forum to accommodate Mexican civil society organizations to address the challenges in theiradvocacies towards the victims of sexual and gender-based violence in Mexico.